1983
DOI: 10.1111/j.1745-4603.1983.tb00330.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Salting of Reconstituted Milk on Curdling by Rennet

Abstract: The addition of sodium chloride to milk is traditionally used in s m areas to prevent microbial and enzymatic spoilage. The efects of salting on the rheologzcal properties of curd have been studied. An increase of the salt content from 0% to 5% induced a progressive decrease of the pH from 6.65 to 6.40 and of the luminosity from 78.23 to 75.68. Clotting and hardening times increased by u p to 8Om0. When pH was adjusted with sodium hydroxide to 6.50 a@r adding salt and before adding rennet, times were increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…Hence, the clotting time showed a minimum around 0.02 M CaCl , while it increased linearly between 0 and 0.12 M NaCl. Our results on enzymic rate and clotting time with NaCl addition agreed with the literature (Ramet et al, 1983;Van Hooydonk et al, 1986;Zoon et al, 1989;Gru!erty & Fox, 1985), though a minimum in clotting time around 0.050 M NaCl has been reported by Alais and Lagrange (1972). According to Dalgleish (1992), ionic strength increase would lead to the screening of negative charge on both enzyme and substrate and to the increase in the rate of proteolysis of -casein, while according to Visser, Van Rooijen and Slangen (1980), ionic strength increase would lead to a screening of the positively charged cluster of -casein and of chymosin, which would bring about a decreased enzymic rate.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Hence, the clotting time showed a minimum around 0.02 M CaCl , while it increased linearly between 0 and 0.12 M NaCl. Our results on enzymic rate and clotting time with NaCl addition agreed with the literature (Ramet et al, 1983;Van Hooydonk et al, 1986;Zoon et al, 1989;Gru!erty & Fox, 1985), though a minimum in clotting time around 0.050 M NaCl has been reported by Alais and Lagrange (1972). According to Dalgleish (1992), ionic strength increase would lead to the screening of negative charge on both enzyme and substrate and to the increase in the rate of proteolysis of -casein, while according to Visser, Van Rooijen and Slangen (1980), ionic strength increase would lead to a screening of the positively charged cluster of -casein and of chymosin, which would bring about a decreased enzymic rate.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have investigated the e!ect of ionic strength increase of milk, through NaCl or CaCl addition, on physicochemical characteristics of milk and on rennet coagulation (Dalgleish, 1983;Ramet, El-Mayda & Weber, 1983;McMahon, Brown, Richardson & Ernstrom, 1984;Gru!erty & Fox, 1985;Van Hooydonk, Hagedoorn & Boerrigter, 1986;Zoon, Van Vliet & Walstra, 1989;Le Graet & BruleH , 1993), but few deal with the e!ect of the reduction of ionic strength towards zero.…”
Section: Introductionmentioning
confidence: 99%
“…In the same study, an addition of NaCl above 0.1 M decreased the curd tension greatly. Ramet et al (1983), Gouda et al (1985 and Awad (2007) found in their investigations that the rennet gel formation and gel firmness decreased when the concentration of the NaCl in milk was increased. In contrast, Jen and Ashworth (1970) reported that an addition of 0.1 M NaCl increased the curd tension, but Grufferty and Fox (1985) observed that the curd tension after 2.5 times the clotting time was not affected by added NaCl up to 0.5 M.…”
Section: Introductionmentioning
confidence: 97%
“…Ramet et al . (), Gouda et al . () and Awad () found in their investigations that the rennet gel formation and gel firmness decreased when the concentration of the NaCl in milk was increased.…”
Section: Introductionmentioning
confidence: 98%
“…However, since NaCl addition to milk also causes a decrease in pH, it was uncertain whether the increase in CT observed was due exclusively to the NaCl addition and not to the drop in pH. Different experiments where the pH was kept constant showed a gradual increase in CT as a function of the NaCl addition (Ramet et al, 1983;Grufferty and Fox, 1985). Another interesting observation was that when NaCl was added to milk, higher rennet concentration was needed to obtain a CT similar to that in milk without any NaCl added.…”
Section: Introductionmentioning
confidence: 96%